Tears Falling on Goosebumps: Co-occurrence of Emotional Lacrimation and Emotional Piloerection Indicates a Psychophysiological Climax in Emotional Arousal - Wassiliwizky, Eugen; Jacobsen, Thomas; Heinrich, Jan; Schneiderbauer, Manuel; Menninghaus, Winfried (Frontiers in Psychology, 2017)
This psychophysiological study is the first to examine the relationship between emotional tears and emotional piloerection (i.e., goosebumps). Although both phenomena have been related to peak states of being moved, details about their temporal occurrence and the associated levels of physiological arousal have remained unknown. In our study, we used emotionally powerful film scenes that were self-selected by participants. Our findings show that even within peak moments of emotional arousal, a gradation of intensity is possible. The overlap of tears and goosebumps signifies a maximal climax within peak moments. On the side of the stimulus, we found that displays of prosocial behavior play a crucial role in the elicitation of tears and goosebumps. Finally, based on the results of a formal film analysis of the tears-eliciting clips provided by our participants, as compared to randomly extracted, equally long control clips from the same films, we show how the technical and artistic making of the clips was optimized for the display of social interaction and emotional expressions.